Overexpression of Adiponectin Receptors in Opium Users with and without Cancer - Firouzabadi N; Haghnegahdar M; Khalvati B; Dehshahri A; Bahramali E (Dove Medical Press, 2020)
Negar Firouzabadi,1– 3 Maral Haghnegahdar,1 Bahman Khalvati,4 Ali Dehshahri,5 Ehsan Bahramali6 1Department of Pharmacology & Toxicology, School of Pharmacy, Shiraz University of Medical Sciences, Shiraz, Iran; 2Pharmaceutical Sciences Research Center, Shiraz University of Medical Sciences, Shiraz, Iran; 3Non-Communicable Diseases Research Center, Fasa University of Medical Sciences, Fasa, Iran; 4Medicinal Plants Research Center, Yasuj University of Medical Sciences, Yasuj, Iran; 5Department of Pharmaceutical Biotechnology, School of Pharmacy, Shiraz University of Medical Sciences, Shiraz, Iran; 6Digestive Disease Research Center, Digestive Disease Research Institute, Shariati Hospital, Tehran University of Medical Sciences, Tehran, IranCorrespondence: Negar FirouzabadiDepartment of Pharmacology & Toxicology, School of Pharmacy, Shiraz University of Medical Sciences, Shiraz, IranTel +98-917-314-5303Fax +98-713-2424128Email nfirouzabadi@yahoo.comAim: Opium addiction is a serious public health concern in the Middle East countries causing various illnesses. Opium use is associated with an increased risk of several cancers; however, the underlying mechanisms are not yet fully elucidated. Altered levels of adiponectin and its related main receptors, Adiponectin receptor 1 and 2 (AdipoR1 and AdipoR2) have been associated with several malignancies. Opium users are at risk of various cancers. All together let us to the hypothesis that probable overexpression of AdipoRs in opium users might be linked to the occurrence of cancer in this population.Methods: One hundred opium users along with 100 healthy non-opium users were enrolled in the study. Opium users were followed up for 5 years (2014– 2019) to evaluate the occurrence of malignancies. AdipoR1 and AdipoR2 expressions were measured using a flow cytometry method.Results: Expression of AdipoR1 and AdipoR2 was significantly higher in opium users compared with the healthy control group (P=0.0001 and 0.0001, respectively). Eight opium users developed cancer during the follow-up period. Subjects abusing opium developed cancer by 8.6 folds comparing to non-opium users (P=0.034; OR=8.6; 95% CI (1.06– 70.1)). Expression of these two receptors was significantly higher in opium users developing cancer compared with cancer-free opium (P=0.001).Conclusion: Considering the significant overexpression of AdipoR1 and AdipoR2 in opium users and in opium users who developed malignancies and the association between upregulation of these receptors in most cancers affecting opium users and assessment of AdipoRs may serve as an early detection tool of cancer in this population.Keywords: opium, addiction, adiponectin, adiponectin receptors, cancer